1997
DOI: 10.1148/radiology.205.1.9314975
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopically triggered contrast-enhanced three-dimensional MR angiography with elliptical centric view order: application to the renal arteries.

Abstract: With this fluoroscopically triggered MR angiographic technique, high-quality, arterial phase, relatively motion immune angiograms can be routinely obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
172
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(178 citation statements)
references
References 23 publications
3
172
0
3
Order By: Relevance
“…More than a decade ago, basic advances were made with the intent of providing a high-quality arterial phase image. These included understanding the effect of missed timing of the acquisition to the contrast material bolus (4), development of methods to provide accurate timing (5)(6)(7), and development of centric phase encoding as a means for allowing high spatial resolution with good venous suppression (8,9). Methods were developed for time-resolved 3D acquisition (10), which in general involved a trade-off of temporal for spatial resolution (11).…”
mentioning
confidence: 99%
“…More than a decade ago, basic advances were made with the intent of providing a high-quality arterial phase image. These included understanding the effect of missed timing of the acquisition to the contrast material bolus (4), development of methods to provide accurate timing (5)(6)(7), and development of centric phase encoding as a means for allowing high spatial resolution with good venous suppression (8,9). Methods were developed for time-resolved 3D acquisition (10), which in general involved a trade-off of temporal for spatial resolution (11).…”
mentioning
confidence: 99%
“…Third, precise timing of the acquisition can further reduce bolus profile artifacts. A robust method for timing the acquisition is "fluoroscopic" scanning of the arriving bolus (18). With this technique, the physician or technologist observes the arrival of the bolus in a real-time "fluoroscopic" scan and triggers the CE-MRA acquisition at the peak of the arterial signal.…”
Section: Contrast-enhanced Mr Angiography (Ce-mra)mentioning
confidence: 99%
“…Some key developments include the advent of 1) high-performance gradient hardware capable of providing repetition times (TR) and echo times (TE) on the order of a few milliseconds, making it possible to acquire moderate resolution CE-MRA images within a breath-hold; 2) real-time fluoroscopic monitoring eliminating the guesswork involved in timing the bolus arrival in the target vasculature (8,9); and 3) centric phase-encode acquisition schemes that capture the arterial enhancement associated with the first pass of the gadolinium (Gd) contrast, with minimal venous contamination even in scans with long acquisition times (10)(11)(12)(13). These developments have contributed to the improved robustness of CE-MRA, and numerous published studies have shown high sensitivity and specificity of CE-MRA for evaluating renal artery disease (1)(2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%